Per capita interactions and stress tolerance drive stress-induced changes in biodiversity effects on ecosystem functions - Jan M. Baert (Nature Portfolio, 2016)
Biodiversity often increases ecosystem functions, but stressors could disrupt that relationship. Using a microalgae model, Baert et al.show how stress-induced changes in the biodiversity–ecosystem function relationships depend on species interactions and stress tolerance.